Review of the New World Tigava Lace Bug Complex (Hemiptera: Heteroptera: Tingidae), with the Description of Two New Genera and Two New Species and a Key to Genera - Henry, Thomas J. (2017)
The lace bug (Tingidae) genera belonging to the New World Tigava complex are reviewed. The two new genera and new species Mexicotingis brailovskyi, from México, and Paraceratotingis convergens, from Venezuela, are described. Diagnoses, descriptions, and digital color photographs of the new taxa, diagnoses and digital photographs of the heads and pronota of all genera, an updated checklist and distributions of the included species, and a key to genera are provided to help distinguish these closely related Tingidae.